Nicotine dependence in community-dwelling Chinese patients with schizophrenia - Yan Li; Chee H Ng; Cai-Lan Hou; Xin-Rong Ma; Yu Zang; Fu-Jun Jia; Kelly Y C Lai; Gabor S Ungvari; Mei-Ying Cai; Yu-Tao Xiang (General Psychiatry)
Background Smoking is a serious public health problem. Patients with schizophrenia usually have a higher prevalence of smoking than the general population, but the level of nicotine dependence is seldom studied, especially for patients living in the communities.Aims This study aimed to examine the level of nicotine dependence in Chinese community-dwelling patients with schizophrenia and explored its associated sociodemographic and clinical factors.Methods A total of 621 patients with schizophrenia treated in the primary care centres of Guangzhou were consecutively recruited. The level of nicotine dependence was assessed with the Chinese version of the Fagerström Test for Nicotine Dependence (FTND).Results 148 patients with schizophrenia were current smokers, and the mean (SD) score of FTND was 5.06 (2.55) for all the current smokers. The prevalence of nicotine addiction was 48.0% (95% CI: 40.0%-56.0%) in patients with current smoking. The patients with schizophrenia had a significantly higher level of nicotine dependence than the Chinese general population. Multiple linear regression analysis revealed that male gender, being unemployed, having a family history of psychiatric disorders, having major medical conditions, first illness episode and less severe positive symptoms were significantly associated with a higher level of nicotine dependence.Conclusion Community-dwelling patients with schizophrenia in China, especially male patients, had a higher level of nicotine dependence than the general population.